2023
DOI: 10.3390/ma16124325
|View full text |Cite
|
Sign up to set email alerts
|

Study on Preparation and Performance of Foamed Lightweight Soil Grouting Material for Goaf Treatment

Abstract: The harm goafs and other underground cavities cause to roads, which could lead to secondary geological hazards, has attracted increased attention. This study focuses on developing and evaluating the effectiveness of foamed lightweight soil grouting material for goaf treatment. The study examines the foam stability of different foaming agent dilution ratios by analyzing foam density, foaming ratio, settlement distance, and bleeding volume. The results show that there is no significant variation in foam settleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Liu et al investigated the effects of foam densities, foaming agent types, and the presence of slurry on the pore structure and mechanical properties of foamed lightweight soils to evaluate their stability [7]. Zhao et al examined the foam stability of different foaming agent dilution ratios by analyzing foam density, foaming ratio, settlement distance, and bleeding volume, developing and evaluating the effectiveness of foamed lightweight soil grouting material for goaf treatment [8]. Chong et al investigated the influence of dry-wet cycles and sulfate attack on the performance of magnesium potassium phosphate cement as well as the effect of waterglass [9].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…Liu et al investigated the effects of foam densities, foaming agent types, and the presence of slurry on the pore structure and mechanical properties of foamed lightweight soils to evaluate their stability [7]. Zhao et al examined the foam stability of different foaming agent dilution ratios by analyzing foam density, foaming ratio, settlement distance, and bleeding volume, developing and evaluating the effectiveness of foamed lightweight soil grouting material for goaf treatment [8]. Chong et al investigated the influence of dry-wet cycles and sulfate attack on the performance of magnesium potassium phosphate cement as well as the effect of waterglass [9].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…Liu et al [5] investigated the effect of gypsum on the performance of alkali slag-fly ash slurry under composite excitation and concluded that under the action of freeze-thaw cycles, the value of the loss of strength of the nodule body was positively correlated with the gypsum dosage, and the loss of strength was the most significant in the first five freeze-thaw cycles. Zhao et al [6] investigated the water stability and frost resistance of a new grouting material for foam lightweight soil, and the results showed that the strength of the specimen decreased with the increase in the number of freeze-thaw cycles, and the larger the water-cement ratio, the weaker the frost resistance of the specimen. Wang et al [7] investigated the sulfate resistance of grouting slurries mixed with lead-zinc tailings.…”
Section: Introductionmentioning
confidence: 99%